Is it the picture or is it the frame? An fMRI study on the neurobiology of framing effects - Silveira, Sarita; Fehse, Kai; Vedder, Aline; Elvers, Katrin; Hennig-Fast, Kristina (Frontiers in Human Neuroscience, 2015)
Using functional magnetic resonance imaging we investigated whether a culturally defined context modulates the neurocognitive processing of artworks. We presented subjects with paintings from the Museum of Modern Art (MoMA) in New York, and labeled them as being either from the MoMA or from an adult education center. Irrespective of aesthetic appreciation, we found higher neural activation in the left precuneus, superior and inferior parietal cortex for the MoMA condition compared to the control label condition. When taking the aesthetic preference for a painting into account, the MoMA condition elicited higher involvement of right precuneus, bilateral anterior cingulate cortex, and temporoparietal junction. Our findings indicate that mental frames, in particular labels of social value, modulate both cognitive and affective aspects of sensory processing.